Governance reconsidered how boards, presidents, administrators, and faculty can help their colleges thrive - Pierce, Susan Resneck 1943- (Jossey-Bass higher and adult education series., 2014)
"Revamp senior administration organization for more effective governance. Governance Reconsidered: How Boards, Presidents, Administrators, and Faculty Can Help Their Colleges Thrive takes an in-depth look at the current practice of governance in higher education and explores solutions for more effective functioning. Written by a former college president, the book provides an insider's perspective on the growing tensions around the traditional shared governance model and identifies the key challenges facing trustees, presidents, senior administrators, and faculty. Traditional shared governance operations are typically time-consuming, process-laden, and slow to respond to the internal and external forces acting upon modern educational institutions. Higher education is facing increasing political and economic pressure, and senior administration frequently needs the flexibility to make institutional decisions quickly. Using recent public scandals as examples, Governance Reconsidered illustrates how the tension between the need for timely decisions and action versus the importance of mission and academic quality is creating a dramatic systemic problem. The book provides practical advice on the issues at the heart of the matter, including: the nature and pace of change on campus, including the pressures facing higher education; clarity about the roles and responsibilities of trustees, the president, and the faculty; the campus community's role in decision-making activities; how thriving universities can govern collaboratively. The book also addresses the brand new challenges that affect higher education governance, including MOOCs, online learning, and rising questions about value and cost. Campus leaders must work together effectively to boost higher education, and Governance Reconsidered contains the questions and answers integral to implementing effective governance"--Provided by publisher.